Guidelines for Manufacturing and Application of Organoids: Lung - Lim, Kyungtae; Lee, Mi Ok; Choi, Jinwook; Kim, Jung Hyun; Kim, Eun Mi; Woo, Chang Gyu; Chung, Chaeuk; Cho, Yong Hee; Hong, Seok Ho; Cho, Young Jae; Ahn, Sun Ju (International Journal of Stem Cells, 2024)
The objective of standard guideline for utilization of human lung organoids is to provide the basic guidelines required for the manufacture, culture, and quality control of the lung organoids for use in non-clinical efficacy and inhalation toxicity assessments of the respiratory system. As a first step towards the utilization of human lung organoids, the current guideline provides basic, minimal standards that can promote development of alternative testing methods, and can be referenced not only for research, clinical, or commercial uses, but also by experts and researchers at regulatory institutions when assessing safety and efficacy.
Keywords: Human lung; Lung organoid; Organoid Standards Initiative